Extramedullary hematopoiesis in the adrenal: Case report and review of literature - Banerji, John Samuel (Canadian Medical Association, 2013)
Extramedullary haematopoiesis (EMH) is common in the spleen, liver and lymph nodes, or in para osseus sites. EMH in the adrenal is rare, with fewer than 10 cases reported. We report the case of a 40-year-old male who underwent laparoscopic adrenalectomy for an incidentally detected adrenal mass. The histology showed extramedullary hematopoesis. In patients with a known history of haemolytic anaemia, an enlarged adrenal gland in an asymptomatic individual could represent extramedullary haematopoesis. A confirmatory biopsy would be all that is necessary to avoid adrenalectomy.